Analisis Pengaruh Variasi Media Pendingin Pengelasan SMAW Terhadap Kekuatan Tarik Baja ST 37 - Haura Muthia Munawar; Iwan Nugraha Gusniar; Ratna Dewi Anjani (Jurnal Ilmiah Wahana Pendidikan, 2022)
Welding is commonly used in manufacturing, one of the processes in welding is the cooling process. The cooling process is carried out against the results of welding steel ST 37 using air, water and oil cooling media. This process aims to fixing the tensile strength value of the welding result ST 37, without changing the composition chemistry. This process includes welding and cooling at a certain speed to obtain the desired properties as well as varying tensile strength values With experimental research methods, the purpose of this study is to find out how the influence of variations in cooling media on the tensile strength of ST37 steel. From some of the cooling media used, it can be seen that a good cooling media is an oil cooling medium, because the average tensile strength is 53,415 kg / mm2. As for the cooling media what produces the greatest tensile strength is the air conditioning media with the average tensile test was 49,764 kg/mm2.